Characterization of ORF19.7608 (PPP1), a biofilm-induced gene of Candida albicans - Iwuchukwu, Nmerichukwu C.; Costa, Anna Carolina Borges Pereira da; Law, Chris; Kim, Min-Ju; Mitchell, Aaron P.; Whiteway, Malcolm (PLOS ONE, 2025)
The opportunistic human pathogen Candida albicans is an important cause of nosocomial infections, in large part because of its propensity to form biofilms on indwelling medical devices such as catheters. The formation of these biofilms is controlled by a complex transcriptional network and involves over a thousand genes, many of which are uncharacterized. We have investigated three genes (ORF19.4654, ORF19.7608, and PBR1), found only in C. albicans and closely related species, that are highly induced under biofilm conditions and encode small proteins with N-terminal signal sequences. Through the construction of fluorescent protein fusions, we have examined the location of the encoded proteins in both planktonic and biofilm cells. Orf19.4654-Scarlet and Pbr1-Scarlet were localized to the vacuole under both conditions. In contrast, the Orf19.7608-GFP fusion generated a punctate pattern only under biofilm conditions and was designated Ppp1 (Punctate Pattern Protein 1). The Ppp1-GFP puncta were similar in location, stability, and size to those formed by the eisosome subunit Sur7, but co-localization studies suggest that Ppp1 and Sur7 define separate elements. The PPP1 mutation does not cause a distinct phenotype under various stress conditions or in the presence of antifungals and does not impact biofilm formation and biomass. These data suggest that while the expression and cellular localization of Ppp1 appear controlled by conditions generating biofilms, and define a unique subcellular localization pattern, Ppp1 protein function is not essential for biofilm formation.